Effectiveness of Multirepresentation-Based E-Modules to Improve Scientific Reasoning Ability on Temperature, Heat, and Expansion Materials for Junior High School Students - Arifiana, Atiah; Mahardika, I Ketut; Wicaksono, Iwan (International Journal of Education, Information Technology, and Others, 2025)
Scientific reasoning is a fundamental ability that students need to develop to face the challenges of the 21st century. This ability plays an important role in understanding science concepts, solving problems, and linking knowledge with everyday life through a systematic scientific process. However, science learning in schools has not had a significant impact on improving these abilities. A number of studies have shown that students' scientific reasoning in Indonesia is still low, hindering a deep understanding of science concepts and their application in real contexts. This condition requires innovative teaching materials that can facilitate students' active involvement, one of which is through multirepresentation-based e-modules. This research aims to develop multirepresentation-based e-modules and assess their effectiveness in improving the scientific reasoning skills of junior high school students. The research method used is Research and Development (R&D) with the ADDIE model. The research subjects were students of class VII F SMP Negeri 7 Jember. The research instruments were pretest and posttest tests to measure scientific reasoning ability. The results showed that the use of multirepresentation-based e-modules was effective in improving students' scientific reasoning skills, indicated by the N-Gain value which was in the high category. Thus, multirepresentation-based e-modules are feasible to use as innovative teaching materials in learning temperature, heat, and expansion.